A Multi-level Review of Engineering Ethics Education: Towards a Socio-technical Orientation of Engineering Education for Ethics. - Martin, Diana Adela; Conlon, Eddie; Bowe, Brian (Science & Engineering Ethics, 2021)
This paper aims to review the empirical and theoretical research on engineering ethics education, by focusing on the challenges reported in the literature. The analysis is conducted at four levels of the engineering education system. First, the individual level is dedicated to findings about teaching practices reported by instructors. Second, the institutional level brings together findings about the implementation and presence of ethics within engineering programmes. Third, the level of policy situates findings about engineering ethics education in the context of accreditation. Finally, there is the level of the culture of engineering education. The multi-level analysis allows us to address some of the limitations of higher education research which tends to focus on individual actors such as instructors or remains focused on the levels of policy and practice without examining the deeper levels of paradigm and purpose guiding them. Our approach links some of the challenges of engineering ethics education with wider debates about its guiding paradigms. The main contribution of the paper is to situate the analysis of the theoretical and empirical findings reported in the literature on engineering ethics education in the context of broader discussions about the purpose of engineering education and the aims of reform programmes. We conclude by putting forward a series of recommendations for a socio-technical oriented reform of engineering education for ethics.